Bangkan Malayan Phatic Expression - Safira, Tiara Putri; Reranta, Redika Cindra (Universitas Teknokrat Indonesia, 2025)
Bangkan Malayan, a dialect of the Malay language spoken by the indigenous people of the Bangka Islands, is integral to their cultural and social communication. This language facilitates familial bonds, community cohesion, and cultural preservation. Like many languages, Bangkan Malay has unique features, including phatic expressions. Phatic expressions are used not to exchange ideas but to build and maintain social contact. Understanding these expressions is essential for fostering social relationships and effective communication. This study analyzes Bangkan Malay phatic expressions, focusing on their forms and functions. Data were collected through natural conversations and interviews with native speakers, ensuring the purity and authenticity of the data. The analysis applied theories by Kridalaksana (2012) and Reranta (2022), classifying phatic expressions into particles, words, phrases, and combined forms. Functions of these expressions were examined through qualitative analysis and experiments with native speakers. The findings reveal various forms and functions of phatic expressions in Bangkan Malay. Particle expressions like /gǝ/, /seɁ/, /jo/, /kɑn/, and /keɁ/